Surface-to-surface calibration of acoustic emission sensors - Lan, Hua (2013)
Acoustic emission (AE) testing is widely employed in robotics technologies due to its non-destructive property. As the major component of AE testing, the AE sensor significantly affects the accuracy and reliability of testing results. To improve the performance of AE testing, it is essential to calibrate the sensitivity of AE sensors in frequency domain. Based on the concept of relative calibration, this paper proposes a surface-to-surface calibration method for AE sensors. This method can obtain the frequency response of AE sensors point by point and the sensitivity in various frequency bandwidths simultaneously. A prototype system is designed and experiments are conducted on the systems with AE sensors. The measurement result is consistent with that obtained with the result from Physical Acoustics Corporation (PAC). To further improve the testing accuracy of the proposed system in frequency domain, the surface-to-surface calibration method is also employed to process and analyze signals in time domain efficiently. Compared with ISO standards, the experimental apparatus structure of the surface-to-surface calibration method is relatively simple, and the operation is more convenient.